Health Impact and Social Value of Interventions, Services, and Policies: A Methodological Discussion of Health Impact Assessment and Social Return on Investment Methodologies - Kathryn Ashton; Lee Parry-Williams; Mariana Dyakova; Liz Green; Liz Green (Frontiers Media S.A., 2020)
Introduction: Assessing the positive and negative impact of policies, services and interventions on health and well-being is of great importance to public health. Health Impact Assessment (HIA) and Social Return on Investment (SROI) are established methodologies which assess potential effects on health and well-being, including social, economic and environmental factors, indicating synergies, and cross-over in their approach. Within this paper, we explore how HIA and SROI could complement each other to capture and account for the impact and social value of an assessed intervention or policy.Methods: A scoping review of academic and gray literature was undertaken to identify case studies published between January 1996 and April 2019 where HIA and SROI methodologies have been used to complement each other previously. Semi-structured interviews were carried out with nine international experts from a range of regulatory and legislative contexts to gain a deeper understanding of past experiences and expertise of both HIA and SROI. A thematic analysis was undertaken on the data collected.Results: The scoping review identified two published reports on scenarios where HIA and SROI have both been used to assess the same intervention. Results from the interviews suggest that both methods have strengths as standalone methodologies. HIAs were noted to be well-structured in their approach, assessing health and well-being in its broadest context. SROI was noted to add value by monetizing social value, as well as capturing the social and environmental impact. Similarities of the two methods was suggested as their strong emphasis on stakeholder engagement and common shared principles. When questioned how the two methods could complement each other in practice, our results indicate the benefits of using HIA as an initial exploration of impact, potentially using SROI subsequently to monetarize social value.Conclusion: HIA and SROI have many synergies in their approaches. This research suggests potential benefits when used in tandem, or combining the methods to assess impact and account for social value. Further research is needed to understand the implications of this in practice, and to understand how the results of the two methods could be used by decision-makers.